The power of peers how the company you keep drives leadership, growth, & success - Leon, Shapiro (Brookline Bibliomotion, 2016)
Birds of a feather flock together. We're all in the same boat. Great minds think alike. While just figures of speech to some, they reflect a simple truth--it's the company we keep that often determines the level of personal growth and professional success we achieve in life. Business leaders exchange information and ideas. They network to make deals and build partnerships. They work together to optimize best practices, and they reach out to leaders outside their companies to accelerate growth. Simply put, CEOs and business leaders provide value to one another that they can't find anywhere else. In The Power of Peers, authors Leon Shapiro and Leo Bottary introduce peer advantage, a concept that transcends peer influence. This is what CEOs and business leaders experience when they are more selective, strategic, and structured in the way they engage their peers. Peer advantage gives CEOs the insights to compete and the courage to act. The Power of Peers features stories of business leaders from a range of industries to illustrate the five essential factors for peer advantage, how it impacts personal growth and why it has proven so effective in helping leaders identify future opportunities and challenges. It's what top, growth-oriented executives have relied upon for decades to be successful in business and in life.
Includes bibliographical references (pages 171-174) and index.
Keywords: Business networks